2018
DOI: 10.1007/s12031-018-1208-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Architecture of the Neuronal Cacng2/Tarpγ2 Gene Promoter: Multiple Repressive Domains, a Polymorphic Regulatory Short Tandem Repeat, and Bidirectional Organization with Co-regulated lncRNAs

Abstract: CACNG2 (TARPγ2, Stargazin) is a multi-functional regulator of excitatory neurotransmission and has been implicated in the pathological processes of several brain diseases. Cacng2 function is dependent upon expression level, but currently, little is known about the molecular mechanisms that control expression of this gene. To address this deficit and investigate disease-related gene variants, we have cloned and characterized the rat Cacng2 promoter and have defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…PXDC1 is a gene for which the function is still poorly known. It was found to be repressed in the liver of mice and rats exposed to a pollutant of the dioxin class (TCDD, or 2,3,7,8-tetrachlorodibenzo-p-dioxin) 57 . Furthermore, it was shown that transcriptional activation of PXDC1 using a CRISPR activation system increased the survival of an acute myeloid leukaemia cell line exposed to cytarabine, a molecule used in standard chemotherapeutic mix for this leukaemia, hence increasing the resistance of the cells to the chemotherapy 58 .…”
Section: Discussionmentioning
confidence: 99%
“…PXDC1 is a gene for which the function is still poorly known. It was found to be repressed in the liver of mice and rats exposed to a pollutant of the dioxin class (TCDD, or 2,3,7,8-tetrachlorodibenzo-p-dioxin) 57 . Furthermore, it was shown that transcriptional activation of PXDC1 using a CRISPR activation system increased the survival of an acute myeloid leukaemia cell line exposed to cytarabine, a molecule used in standard chemotherapeutic mix for this leukaemia, hence increasing the resistance of the cells to the chemotherapy 58 .…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be clarified how the ZMYM3 GA-STR complex functions in the human brain. From what we know so far, GA-STRs of the range observed in the ZMYM3 complex can dramatically alter gene expression 32,33 . ZMYM3 is among the top three master regulators causally responsible for regulating the transcriptional signature of AD progression 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known regarding the molecular mechanisms that control its expression. The rat Cacng2 promoter was recently cloned, and its fundamental features include multiple RE-1 silencing transcription factor (REST) domains and a Ca 2+ regulatory element-binding factor (CaRE) element ( Corney et al, 2019 ). It also regulates the transcription of Ca V γ 2 /Stg in the antisense direction of the genome, while in the sense direction controls the transcription of a lncRNA ( Corney et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the presence of functional CRE sites, it was reasonable to propose a possible modulation through the activation of a G protein-coupled receptor. It is well known that when this type of receptors is activated by its ligand, a nucleotide exchange occurs in the Gα subunit, and a conformational change is induced in the Gαβγ complex that results in its dissociation into two active signaling molecules, the Gα-GTP subunit and the Gβγ dimer ( Corney et al, 2019 ). The Gα-GTP subunit, in turn, activates a wide range of signaling pathways that include the participation of adenylate cyclase (AC) and several protein kinases that phosphorylate a wide variety of effectors.…”
Section: Introductionmentioning
confidence: 99%